2016
DOI: 10.20960/nh.806
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic: effectiveness nutrition in cancer treatment and prevention

Abstract: Key words:Colorectal cancer. Infl ammatory bowel disease. Probiotics. Intestinal microbiota. Immune system. Palabras clave:Cáncer colorrectal. Enfermedad infl amatoria intestinal. Probióticos. Microbiota intestinal. Sistema inmune. ResumenEntre las neoplasias, el cáncer colorrectal es una de las principales causas de muerte por cáncer en hombres y mujeres. El aumento de la incidencia de este tipo de cáncer es debido al aumento de la esperanza de vida de la población y al aumento de las enfermedades infl amator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 96 publications
0
19
0
Order By: Relevance
“…Over the past three decades, probiotic potential of some bacteria has been well-recognized. The beneficial effects of probiotic bacteria are mainly associated with the maintenance of a healthy gut microbiota, an improvement of gut resilience, the modulation of lactose intolerance, bowel function, and gastrointestinal (GI) comfort, and diarrhea prevention and symptom alleviation (Licciardi et al, 2010 ; Waitzberg et al, 2015 ; Wright et al, 2015 ; Kich et al, 2016 ; Mokoena et al, 2016 ). Probiotic food products, including probiotic powders and probiotic fermented food, account for a significant part of the functional foods in market (60–70% of the total functional food in market; García-Ruiz et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past three decades, probiotic potential of some bacteria has been well-recognized. The beneficial effects of probiotic bacteria are mainly associated with the maintenance of a healthy gut microbiota, an improvement of gut resilience, the modulation of lactose intolerance, bowel function, and gastrointestinal (GI) comfort, and diarrhea prevention and symptom alleviation (Licciardi et al, 2010 ; Waitzberg et al, 2015 ; Wright et al, 2015 ; Kich et al, 2016 ; Mokoena et al, 2016 ). Probiotic food products, including probiotic powders and probiotic fermented food, account for a significant part of the functional foods in market (60–70% of the total functional food in market; García-Ruiz et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated the ability of living cells of mutant S.boulardii (MSb) to promot the level of IL-10 more than commercial (CSb) and local (LSb) S.boulardii. Some factors derived from S.boulardii cells walls have contributed to the enhancement and increase of the host's immune response and the balance between Th2/ Th1, which has promoted increased IL-10 production (24,25). Besides βglucan, which is derived from the walls of the dead cells of S.boulardii yeast in intestinal tract, has a strong effect in stimulating and increasing the immune response by binding to special receptors, especially in the gastrointestinal tract such as (TLR-2), Tall Like Receptor, Dectin-1 receptor and other receptors, stimulating immune cells to produce antiinflammatory cytokines IL-10 (26).…”
Section: -Effect the Sboulardii In The Levels Of Il-10 And Ifn-ɣmentioning
confidence: 99%
“…Epidemiological studies have shown that the composition of CRC patients microbiota is different to the one present in healthy population [ 76 ]. Taking into account the effectiveness of probiotics in modulating microbiome composition, the design of microbiota-targeting therapies is now considered as a feasible strategy in the clinic, both as a preventive and a therapeutic approach [ 77 ].…”
Section: Lipid Metabolism Diet and Colorectal Cancermentioning
confidence: 99%